3D printed ceramic phosphor and the photoluminescence property under blue laser excitation. Issue 8 (July 2019) - Hu, Song; Liu, Yingli; Zhang, Yunli; Xue, Zhenhai; Wang, Zhengjuan; Zhou, Guohong; Lu, Chunhua; Li, Hongshu; Wang, Shiwei
Abstract: An Al2 O3 /YAG: Ce 3+ ceramic phosphor was fabricated for high-flux laser lighting using the digital lighting process (DLP)-based 3D printing method for the first time. The photocurable ceramic suspension for 3D printing was prepared by blending well-treated Al2 O3 /YAG: Ce 3+ composite powders with photosensitive resin monomers and photo-initiators. The printing parameters, debinding and sintering processes were designed delicately to fabricated the dense sub-millimeter-sized cylinder ceramic with high dimensional accuracy. The ceramic showed excellent luminescence property under blue laser excitation with a threshold of 20.7 W/mm 2, higher than that prepared via dry-pressing followed by vacuum sintering. The luminescence properties and the microstructures of both ceramics were further comparatively investigated to find the possible interpretations for improvement of laser flux for the 3D-printed ceramic. The present work indicated that the new developed 3D printing method was promising for preparing luminescent ceramics for high-flux laser lighting in a rapid, effective, low-cost and precision-controlled manner.